The Influence of Commedia Dell’arte is Evident in the Opera: Don Giovanni - Furkan Aktakka (Konservatoryum)
The study looks at the opera Don Giovanni, written by Lorenzo da Ponte and composed by W.A. Mozart, and how it was influenced by commedia dell’arte. The study looks at the historical process of the figure of Don Juan, which emerged in the Spanish Golden Age writer Gabriel Tellez’s work El burlador de Sevilla y convidado de piedra. It also looks at how the commedia dell’arte effects of the Italian folk theater tradition and the reflections of the commedia dell’arte effects on the figure of Don Juan on the opera Don Giovanni. The study used a qualitative research method and a literature review. It looked at Turkish and English texts about Don Juan, commedia dell’arte, Don Giovanni, and their interactions. The research found that some interpretations of Don Juan include commedia dell’arte. The opera Don Giovanni shows that the character of Leporello is like a comic servant. This shows that the opera is influenced by commedia dell’arte. The opera also shows that Leporello uses disguise, plays the mandolin and uses small comic lines.